2011
DOI: 10.1136/sextrans-2011-050109.134
|View full text |Cite
|
Sign up to set email alerts
|

O3-S6.02 Screening forMycoplasma genitalium,Chlamydia trachomatisandBacterial vaginosisin a public hospital, pregnancy termination service

Abstract: participant demographic or behavioural characteristics between arms. Adherence to study medication did not differ between arms: 382 (91%) took all or most oral metronidazole and 330 (80%) all or most vaginal therapy. Retention rates were high, with 77 (17%) lost to follow-up over 6 months, and did not differ between arms. Participants contributed 153.7 person years of follow-up to analyses. On exit survey 88% of participants did not know or correctly guess the vaginal therapy they had received. Six month cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…6 A surveillance study at the Royal Women’s Hospital Melbourne (2011) of 1627 women undergoing surgical termination of pregnancy (mean age 26.4 years) found the prevalence of Mg to be 4.6% and the prevalence of Ct 5.3% in this population. 7 A study in the United Kingdom found 4.5% of asymptomatic female and male patients attending a sexual health clinic over a six-month period to be positive for Mg . 8 Both these studies highlight the potential value of testing for Mg in asymptomatic people at risk of STI.…”
Section: Introductionmentioning
confidence: 99%
“…6 A surveillance study at the Royal Women’s Hospital Melbourne (2011) of 1627 women undergoing surgical termination of pregnancy (mean age 26.4 years) found the prevalence of Mg to be 4.6% and the prevalence of Ct 5.3% in this population. 7 A study in the United Kingdom found 4.5% of asymptomatic female and male patients attending a sexual health clinic over a six-month period to be positive for Mg . 8 Both these studies highlight the potential value of testing for Mg in asymptomatic people at risk of STI.…”
Section: Introductionmentioning
confidence: 99%